Prenatal stress promotes insulin resistance without inflammation or obesity in C57BL/6J male mice - Quiroga, Sofia (2021)
Fil: Quiroga, Sofia. Pontificia Universidad Católica Argentina. Instituto de Investigaciones Biomédicas; Argentina